2019
DOI: 10.1108/cpoib-03-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of addressing stakeholders’ expectations through corporate non-market strategies in emergent countries

Abstract: Purpose This paper aims to examine the tensions between global and local corporate social responsibility (CSR) initiatives developed by multinationals managing subsidiaries in different emergent countries. Multinationals carry out a wide array of political activities (Boddewyn and Brewer, 1994; Hillman and Hitt, 1999; Rehbein and Schuler, 1995) supporting their economic objectives, even though the political landscape and the institutional environment may vary significantly in the different countries in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…MNC legitimacy acquisition means that MNCs’ overseas business activities conform to the social and moral expectations of the host country, which helps to improve the host country's public attitude toward MNCs (Kaya and Walker, 2012) and maintain a good reputation in the local industry (Fombrun et al , 2000). Improving legitimacy through non-market strategies contributes to mediating tensions between MNCs and host countries, avoiding conflicts (Saïd et al , 2019), and thus preventing overseas compliance risks.…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…MNC legitimacy acquisition means that MNCs’ overseas business activities conform to the social and moral expectations of the host country, which helps to improve the host country's public attitude toward MNCs (Kaya and Walker, 2012) and maintain a good reputation in the local industry (Fombrun et al , 2000). Improving legitimacy through non-market strategies contributes to mediating tensions between MNCs and host countries, avoiding conflicts (Saïd et al , 2019), and thus preventing overseas compliance risks.…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…Stakeholder theory was found in isolation in 6 studies and we identified combinations with RDT. This theoretical perspective places the firm at the center of a network of relationships with stakeholders, demonstrating that they need to respond to their claims and that performance can be improved through the management of favorable relationships (He, Tian, & Chen, 2007;Parnell, 2015;Saïd, Sevic, & Phillips, 2019). Firms weigh the power and interest that stakeholders exercise, prioritizing claims according to different relationships and their complexities, and more efficiently allocating firm resources to this end (Lucea & Doh, 2012;Mbalyohere & Lawton, 2018).…”
Section: Stakeholder Theorymentioning
confidence: 99%
“…This does not meet local needs in a collaborative and transparent manner, as advocated by Tang-Lee (2016). Saïd et al (2018) also noted that a better dialogue with external stakeholders minimizes the risks to projects.…”
Section: Csf 9: Ability To Analyse Risks That May Compromise the Success Of The Projectmentioning
confidence: 99%